Avaliação biomecânica comparativa da técnica de TPLO com uso de parafusos bicorticais ou monocorticais em modelos sintéticos de tíbia de cães - Perez Neto, Daniel Munhoz Garcia (2025)
Cranial cruciate ligament (CrCL) disease is the leading cause of lameness in dogs. Among the surgical treatment options, tibial osteotomy techniques are considered the gold standard, with particular emphasis on tibial plateau levelling osteotomy (TPLO). The aim of this study was to evaluate the mechanical resistance of the TPLO plate-screw construct fixed with either bicortical or monocortical proximal screws of varying lengths in synthetic canine tibial bone models. The study comprised a compressive biomechanical test, with specimens allocated into four groups, each containing six samples. Stabilisation was achieved using the TPLO technique, varying the length of the screws used for proximal plate fixation. Group G bicortical was treated with bicortical proximal screws (control), whereas groups G 75%, G 50%, and G 25% received monocortical screws with 75%, 50%, and 25% of the transcortical length, respectively. The variables analysed were: maximum load (ML), displacement at maximum load (DML), load at collapse (LC), displacement at collapse (DC), compressive strain (CS), and energy (E). In comparative testing against the control group (G bicortical), no significant differences were observed in any variable for G 75%; G 50% did not differ in ML and LC, but showed reductions in the remaining variables; G 25% exhibited reduced performance across all variables. When comparing the groups among themselves, no differences were observed between G 75% and G 50% in ML and LC; however, G 25% showed significantly lower values than the other groups. For the variables DML, DC, CS, and E, no differences were noted between G 50% and G 25%, but both showed reduced values compared to G 75%.According to the methodology employed in this study, it can be concluded that proximal plate fixation in the TPLO technique using screws with 75% of the transcortical diameter provides biomechanical performance comparable to bicortical screws. Monocortical screws with 50% of the transcortical length demonstrated comparable biomechanical performance to bicortical screws only in certain variables, whereas monocortical screws with 25% of the transcortical length exhibited inferior performance in all variables analysed.